Warrior - Sebert, Kesha ([Australia] RCA/Jive Sony Music Entertainment [distributor], 2012)
Kesha is an exciting new artist signed 22 year old unlike any other. She is outrageous/fun/pop/punk/attitude. Her music is described as a cross between Beastie Boys and Madonna. She was featured on Flo-Rida's single 'Round Round' that sold a record-breaking 636,000 digital tracks in its first week out in the US and over 2.6 million to date. She is also on another track 'Touch Me' on his album 'R.O.O.T.S'. Her debut album is an edgy collection of hard hitting electro-pop songs, made all the more irresistible by their high-octane punk energy and Kesha's irreverent lyrics and attitude.
Warrior; Die Young; C'mon; Thinking Of You ; Crazy Kids; Wherever You Are; Dirty Love; Wonderland; Only Wanna Dance With You; Supernatural; All That Matters (The Beautiful Life); Love Into The Light; Last Goodbye; Gold Trans Am; Out Alive; Past Lives.
Keywords: Popular music -- United States -- 2001-2010.